C02 Analysis of the instability of the CAG trinucleotide repeat and the age of onset in a Huntington's disease population from the Basque country. (16th November 2010) - Valcárcel, L; Kortajarena, J; García, M; Fernández, J M; Lezcano, E; Losada, J; Ruiz, J; Álvarez, A; Pérez, J M; Iriondo, M; Aguirre, A
Abstract : Background: The instability of the CAG trinucleotide repeat from the Huntington's disease (HD) gene is well defined in the germline and it is related to intergenerational changes in the CAG length and the age of onset (AOO), but what about the somatic cells? Recently, it has been suggested that the instability of the CAG repeat in the brain can be a modifier of the AOO and also that there could exist a correlation between other somatic tissue's instability of the CAG and the AOO. Aim: To find the implication of the CAG repeat instability levels (mosaicism levels) of blood cells in the AOO of motor symptoms, cognitive symptoms and/or psychiatric symptoms. Methods: We collected DNA samples and clinical data from 86 individuals with the expanded allele (50 symptomatic and 36 presymptomatic individuals). To measure the mosaicism levels we did several amplifications and cloning of each sample and we also used the densitometry index (DI) method. Results: Although DI correlates negatively and significantly with each AOO, the blood DI does not contribute to explain any of the AOO. Interestingly, we detected differences between DI of symptomatic and presymptomatic individuals and between individuals with and without cognitive symptoms. Conclusion: We can only conclude that, with our analysis method, blood DI does not explain any of the AOO, but it seems to have something to do with cognitive symptoms. More studies are needed to elucidate this matter.